EVALUASI RANAH SIKAP BERBAHASA TERHADAP PEMAHAMAN LITERASI SISWA SEKOLAH DASAR PADA CERITA RAKYAT “BATU MENANGIS” - Firdaus, Ahmad; Mabruroh, Mabruroh; Shofia Zahra Agustina; Yuyu Yuhana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study focuses on the analysis of literacy understanding in folklore. Folk poetry is a part of oral literature that is widely found around the student environment. In the cognitive development of students, folklore is one of the teaching materials that can increase students' understanding of the surrounding area. Thus, it can be analyzed simultaneously related to the evaluation of the realm of students' language attitudes towards literacy understanding from the folklore read. This study is quantitative research with a descriptive research design. The researcher described the students' language attitude towards literacy understanding from the folklore "Batu Menangis". The population in this study is 30 students in class IV SD Unggulan Uswatun Hasanah. Data collection was carried out with a questionnaire on language attitudes and literacy comprehension. The data analysis in this study uses a statistical calculation method with the help of the SPSS 21 program. The results of the research analysis show that it can be categorized that students' attitudes towards understanding story literacy are included in the good category. The data was obtained that of the total research subjects, there were 10 subjects who had a very good assessment of Indonesian language attitudes. The results of the above analysis also show that there is a desire for students to reflect on themselves to contribute to the development of the Indonesian language is still very good. By understanding the realm of language affective in literacy understanding, students can implement it in their environment.